A pair of pears and an orange - McGregor, Anna (Scribble, 2021)
A pair of pears rocked on a seesaw. A pair of pears played ping-pong. A pair of pears rode their tandem bike. Until one day, someone new wanted to join their fun. Big Pear and Little Pear love playing together. But when Orange joins in, their games don't work and Big Pear feels left out. A relatable, hilarious, and kind-hearted tale about navigating friendship when three definitely starts to feel like a crowd! From the author of much-loved Anemone is not the Enemy